Morphological Feature Distances among the Spectral Types of SDSS Galaxies - Duho Kim; Garreth Martin (The Astrophysical Journal)
This study investigates the morphological feature distances among various spectral types of galaxies from the Sloan Digital Sky Survey, including strong and weak active galactic nuclei (AGN), quasi-stellar objects (QSOs), quiescent, and star-forming galaxies. We evaluated the clustering and relative distances of these spectral types in the multidimensional morphological feature space. The results indicate that AGN and QSOs are more closely associated with quiescent galaxies than with star-forming ones, indicating a potential regulation of star formation by AGN activity. Furthermore, the analysis underlines the role of AGN feedback in the dwarf regime having ∼10%–50% closer distances from AGN types to the quiescent type than to the star-forming type in the dwarf regime −18 > M _r > −20, compared to <15% closer in the massive regime M _r < −21. The continuous probability analysis of spectral types being Hubble types upholds the distance analysis results having a range of the probability distribution of AGN types similar to the quiescent type, especially in dwarf galaxies.